2021
DOI: 10.47280/revfacagron(luz).v38.n3.10
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and distribution of plant parasitic-nematodes on golf courses in localities of Baja California Sur, Mexico

Abstract: Golf is a tourist attraction in Baja California Sur (BCS), Mexico. However, the quality of its fields is detracted by presenting yellowing and death on tufgrass. Plant parasitic nematodes are one of the main limitations around the world. However, in BCS, its presence is unknown. In order to determine the diversity and distribution of phytonmatodes in golf courses in BCS, soil samples were collected in four courses. Nematode extraction was done using the Baerman funnel technique. Specimens were identified at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Prior to this work, there have been several research papers illustrating a broad diversity of nematodes associated with turfgrasses in the United States [5,10,11,28,62], Canada [7,63,64], Argentina [65], Germany, Sweden, Norway [66,67], Belgium [8], Israel [68] and Korea [6]. Previous research showed that the species of Hemicriconemoides and Tylenchorynchus associated with turfgrasses include H. chitwoodi Esser, 1960 and H. wessoni Chitwood & Birchfield, 1957 in Cynodon dactylon [10,11]; H. brachyurus (Loos, 1949) Chitwood & Birchfield, 1957 in Poa pratensis and Zoysia japonica [6]; T. claytoni Steiner, 1937 in P. pratensis and Z. japonica [6,10,11]; T. dubius in Agrostis stolonifera and P. pratensis [69]; T. annulatus in Z. japonica; and T. thermophilus in Z. japonica and P. pratensis [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to this work, there have been several research papers illustrating a broad diversity of nematodes associated with turfgrasses in the United States [5,10,11,28,62], Canada [7,63,64], Argentina [65], Germany, Sweden, Norway [66,67], Belgium [8], Israel [68] and Korea [6]. Previous research showed that the species of Hemicriconemoides and Tylenchorynchus associated with turfgrasses include H. chitwoodi Esser, 1960 and H. wessoni Chitwood & Birchfield, 1957 in Cynodon dactylon [10,11]; H. brachyurus (Loos, 1949) Chitwood & Birchfield, 1957 in Poa pratensis and Zoysia japonica [6]; T. claytoni Steiner, 1937 in P. pratensis and Z. japonica [6,10,11]; T. dubius in Agrostis stolonifera and P. pratensis [69]; T. annulatus in Z. japonica; and T. thermophilus in Z. japonica and P. pratensis [6].…”
Section: Discussionmentioning
confidence: 99%
“…Several surveys of nematodes associated with turfgrasses have been conducted in the USA and other countries, and have shown a broad diversity with different countries and regions [5][6][7][8][9][10][11]. In Florida, USA, common genera of nematodes that damage turf include ectoparasitic Belonolaimus, Trichodorus, Nanidorus, Helicotylenchus and Mesocriconema, and endoparasitic Hoplolaimus and Meloidogyne [5].…”
Section: Introductionmentioning
confidence: 99%